Pandangan Al-Qur’an tentang Demokrasi: Analisis Tafsir Maudhu’i - Dzu Hulwin; Ghina Mutmainnah; Hafizah Irfani Azkiah; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this research is to study more broadly related to This study aims to discuss contemporary issues of democracy that are relevant to the Qur'an. This research is a qualitative research with descriptive method and maudhu'i interpretation. The formal object of this research is the science of the Al-Qur’an and contemporary issues, while the material object is verses in the Al-Qur’an about democracy. Democracy in the Al-Qur’an is something that is important and principled, because democracy is a form of deliberation that will produce an agreement, namely consensus. The Al-Qur’an has also explained what principles must exist in a democracy, namely in surat ash-Syuara', an-Nahl, al Hujurat, an-Nisa'. This is also in line with the principles of democracy in Indonesian state law, namely direct, responsible, honest and fair which is abbreviated as